2011
DOI: 10.1186/1465-9921-12-131
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of lung inflammation and fibrosis in CD69-deficient mice after intratracheal bleomycin

Abstract: BackgroundCluster of differentiation 69 (CD69), an early activation marker antigen on T and B cells, is also expressed on activated macrophages and neutrophils, suggesting that CD69 may play a role in inflammatory diseases. To determine the effect of CD69 deficiency on bleomycin(BLM)-induced lung injury, we evaluated the inflammatory response following intratracheal BLM administration and the subsequent fibrotic changes in wild type (WT) and CD69-deficient (CD69-/-) mice.MethodsThe mice received a single dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
(39 reference statements)
2
28
0
Order By: Relevance
“…, an early activation marker antigen on T and B cells, is also expressed on activated macrophages and neutrophils. It was found that CD69-deficient mice developed less bleomycin-induced lung injury and inflammation vs. wild type mice [36]. In our study, the number of CD69 positive granulocytes (Fig.…”
Section: Fig 2 Clinical and Macroscopic Features Of Iodoacetamide-isupporting
confidence: 55%
“…, an early activation marker antigen on T and B cells, is also expressed on activated macrophages and neutrophils. It was found that CD69-deficient mice developed less bleomycin-induced lung injury and inflammation vs. wild type mice [36]. In our study, the number of CD69 positive granulocytes (Fig.…”
Section: Fig 2 Clinical and Macroscopic Features Of Iodoacetamide-isupporting
confidence: 55%
“…2A) and the quantification of Picrosirius red staining (Fig. 2B) as well as protein levels indicate expression of collagen I and III in the alveolar walls is much like those observed in infants with BPD and in animal models of pulmonary fibrosis (31,41,59). Consequently, we speculated that the increases in collagen observed in our model are more likely a deficiency in matrix remodeling rather than a dysregulation in deposition.…”
Section: Discussionmentioning
confidence: 58%
“…Bronchoalveolar lavage (BAL) of mice was performed as describe elsewhere (40). In brief, the trachea was exposed and lavaged three times with 1 ml of PBS.…”
Section: Methodsmentioning
confidence: 99%